Prediction of short-term prognosis of patients with hypertensive intracerebral hemorrhage by radiomic-clinical nomogram - Wang, Jing; Zhou, Lu; Chen, Yuanyuan; Zhou, Hongli; Tan, Yuanxin; Zhong, Weijia; Zhou, Zhiming (Frontiers in Neurology, 2023)
Hypertensive intracerebral hemorrhage (HICH) is the most common type of spontaneous intracerebral hemorrhage in China, with a high mortality and disability. We sought to develop and validate a noncontrast computed tomography (NCCT)-based nomogram to achieve short-term prognostic prediction for HICH patients. We retrospectively studied 292 patients with HICH from two medical centers and they were divided into training cohort (n = 151), validation cohort (n = 66) and testing cohort (n = 75). Based on radiomics analysis, univariate and multivariate analysis, and logistic regression analysis, four models (black hole sign, clinical, radiomics score and combined models) were established to predict prognosis of HICH patients on 30 days after onset. The results suggested the combined model had the best predictive performance with the area under the receiver operating characteristic curve (AUC) of 0.821, 0.816 and 0.815 in the training, validation and testing cohorts respectively. And it was visualized as a radiomics-clinical (R-C) nomogram. Calibration curve analysis showed that the R-C nomogram had satisfactory calibration in the three cohorts. Decision curve analysis demonstrated the R-C nomogram was clinically valuable. Our results suggest the R-C nomogram can accurately and reliably predict the short-term prognosis of HICH patients and provide a useful evaluation for making individualized treatment plans in the next step.